Education of the Future Pedagogues in Higher Pedagogical Educational Establishment (1920-1991) as a Subject of Historic-Pedagogical Research - Inna Yashchuk (Pedagogical Discourse, 2013)
In the presented material, historiographical review of the scientific literature on the problems of student education in higher educational institutions of Ukraine of the twentieth century has been done. The article analyzes periods of 1920-s – 1990-s in the history of domestic higher pedagogical school in the context with the development of the educational system, formation of the Soviet system of educational work as a holistic pedagogical phenomenon. Attention is paid to the fact that the educational process in higher education establishment is a component of the higher educational development, and the education of future teachers in higher educational institutions of Ukraine in the 1920-s –1990-s can be the specific subject of historical and pedagogical research, with its own characteristics: features, aspects and stages of their development. The views of the authors who dealt with certain aspects of the above mentioned problem have been cleared out.